ISSUES OF THE INFLUENCE OF LABOR MIGRATION ON HUMAN DEVELOPMENT - Maloxat Saipovа (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the author interprets labor migration as a long-standing phenomenon and reflects on its positive and negative impact on human development. As part of his research, he also draws conclusions based on the analysis performed.